Penerapan Kurikulum Merdeka pada Pembelajaran PPKn di MA Syekh Subakir Nglegok - Elsa Liana; Suhartono Suhartono; Suryanti Suryanti (Universitas Palangka Raya, 2025)
This study aims to examine how the Independent Curriculum is implemented in Pancasila and Citizenship Education (PPKn) learning at MA Syekh Subakir Nglegok. The method used is descriptive qualitative, with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the formulation of learning objectives and the use of learning media in the Independent Curriculum are able to encourage students to be actively involved, participate in contextual and meaningful learning activities, and face challenges that are in accordance with everyday life. In addition, the implementation of these learning objectives and media also supports student involvement in a more interesting, innovative, and contextual learning process. In other words, the implementation of the Independent Curriculum at MA Syekh Subakir Nglegok has been in line with the constructivism approach, which encourages the creation of a deeper and more meaningful learning experience for students. Based on the results of the study, it can be concluded that the Independent Curriculum has made a positive contribution to the PPKn learning process at the school. These findings are expected to be a reference for educators, schools, and other stakeholders in improving the quality of the implementation of the Independent Curriculum and designing learning strategies that are more innovative and responsive to the needs of the times.